Is R&D Good for Employment? Microeconometric Evidence from the EU - Mariacristina Piva; Marco Vivarelli (Institute of Labor Economics (IZA), 2017)
Using a unique firm-level database comprising the top European R&D investors over the period 2002-2013 and running LSDVC estimates, this study finds a significant labour-friendly impact of R&D expenditures. However, this positive employment effect appears limited in magnitude and entirely due to the medium-and high-tech sectors, while no effect can be detected in the low-tech industries. From a policy point of view, this outcome is supporting the EU2020 strategy, but taking into account that most of European economies are specialized in low-tech activities is also worrying in terms of future perspectives of the European labour market.
Keywords: O33; 330; R&D; innovation; employment; firm-level analysis; EU